2011
DOI: 10.5430/jms.v2n4p35
|View full text |Cite
|
Sign up to set email alerts
|

Internal Versus External Staffing in Nigeria: Cost-Benefit Implications

Abstract: The internal recruitment is perceived in some quarters as the most favourite source of staffing an organization in stable and developed companies. The system needs a strong support from other HR processes in order to enhance morale and promote productivity otherwise it could yield disappointed and unproductive employees in the organization. Such HR processes include effective succession planning and consistent performance management to ensure success of the internal staffing. Though internal staffing may not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
(1 reference statement)
0
3
0
2
Order By: Relevance
“…On the other side, in research conducted by Galbraith et al (2012), library employees indicated that they strongly preferred external leaders because outside candidates can bring a fresh perspective and new ideas into the library. This is crucial because of its help to increase the productivity of the organisation (Anyim et al, 2011). This means that external recruitment (outside libraries altogether) aims to bring new candidates with capacity and desire to develop and advance into the organisation (Deards and Springs, 2014).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…On the other side, in research conducted by Galbraith et al (2012), library employees indicated that they strongly preferred external leaders because outside candidates can bring a fresh perspective and new ideas into the library. This is crucial because of its help to increase the productivity of the organisation (Anyim et al, 2011). This means that external recruitment (outside libraries altogether) aims to bring new candidates with capacity and desire to develop and advance into the organisation (Deards and Springs, 2014).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Kinerja karyawan akan optimal jika organisasi mampu menciptakan kondisi yang dapat mengakibatkan karyawan disiplin dalam bekerja dan memungkinkan karyawan untuk mengembangkan dan meningkatkan kemampuan serta keterampilan yang dimiliki secara optimal (Sumarauw dkk., 2014). Anyim et al (2014) dalam penelitiannya menemukan fakta bahwa penilaian dalam prestasi kerja digunakan untuk menentukan kemungkinan karyawan dipromosikan ke jabatan yang lebih tinggi.…”
Section: Pendahuluanunclassified
“…Sikap loyal diperlukan agar karyawan tersebut dapat bekerja tidak hanya untuk dirinya sendiri tetapi juga untuk kepentingan perusahaan. Sikap loyalitas kerja ini berasal dari kesadaran yang tinggi bahwa antara karyawan dengan perusahaan merupakan dua pihak yang saling membutuhkan (Anyim et al, 2014). Karyawan mesti diperlakukan secara layak dan adil, sehingga mereka dapat betah dalam melaksanakan tugas, disamping bersungguh-sungguh dan penuh tanggung jawab serta berdisiplin.…”
Section: Pendahuluanunclassified
“…External recruitment is when people are recruited from outside the organization to occupy vacant positions (Royal and Althauser, 2003) whilst internal recruitment is when an organization recruits within its ranks to fill vacant positions (Bidwell, 2011;Anyim et al, 2011). For Bidwell (2011), internal recruits perform better than external hires, even though they cost less and are often paid less.…”
Section: Recruitment and Resource-based Theorymentioning
confidence: 99%